Characterization of bovine unconventional memory-like responses induced by Mycobacterium bovis infection and vaccination - Guerra-Maupome, Mariana (Kansas State University, 2019)
Tuberculosis (TB) remains a leading cause of death from infectious diseases worldwide. Mycobacterium bovis is the causative agent of bovine tuberculosis (bTB) and zoonotic TB infection. CD4 T cells are necessary for host defense against M. bovis; however, CD4 T cell-mediated immunity is not sufficient to prevent or eliminate the infection and additional components of the immune system are required for optimum host protection. The innate immune system has long been considered primitive and nonspecific, thought to lack the capacity to mount immunological memory. However, evidence suggests that the innate immune system can improve with pathogen exposure and adopt memory-like traits, potentially conferring resistance to TB, as well as other unrelated diseases. The focus of this thesis was to characterize two types of nonconventional memory responses in calves responding to M. bovis vaccination or virulent infection. Gamma Delta (GD) T cells are unconventional T cells that play a major role in defense against pathogens, especially at mucosal sites such as the lower respiratory tract. GD T cells participate in the response to M. bovis vaccination and infection. In the second chapter, we demonstrate that in cattle, virulent M. bovis infection elicits memory-like responses in circulating mycobacteria-specific GD T cells, characteristic of central memory (TCM) cells which have been reported in humans. We further show that bovine M. bovis-specific circulating GD T cells upregulate the surface expression of lung-homing receptors CXCR3 and CCR5, suggesting that GD have the capacity to home to sites of infection and participate in control of TB infection. In the third chapter, we expand upon our previous studies through a comparative assessment of the phenotype and function of M. bovis-specific GD T cells in the systemic and mucosal compartment following M. bovis Bacille Calmette Guerin (BCG) vaccination. We show that aerosol BCG immunization induces both systemic and mucosal M. bovis-specific γδ T cells with a surface phenotype associated with highly differentiated TCM and effector memory (TEM) cells, respectively. Evidence from epidemiological studies in humans suggests that previous exposure to M. bovis BCG, a live attenuated vaccine, reduces the risk of childhood mortality due to prevention of sepsis, diarrhea and respiratory infections. It has been suggested that the nonspecific disease resistance induced by BCG is mediated by an enhanced memory-like response of the innate immune system known as ‘trained’ immunity. In the fourth chapter, we demonstrate that in vitro and in vivo infection with M. bovis BCG elicits long-term memory-like traits in bovine circulating innate cells, but not lung resident populations, during secondary in vitro Toll-like receptor (TLR) challenge. Consistent with reports in other species, this cellular hyperresponsiveness correlated with a metabolic shift towards glycolysis. Together, our research suggests that effective control of M. bovis infection requires not only properly activated adaptive immune responses but may also benefit from nonconventional memory-like responses from populations such as ‘trained’ innate monocytes and differentiated GD T cells. Our results have important implications towards the development of novel intervention strategies for use against TB and related respiratory infections in humans and animals alike.
Keywords: Mycobacterium bovis; Immune response; cattle